2017
DOI: 10.7324/japs.2017.70325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and awareness of over the counter use of non-steroidal anti-inflammatory drugs

Abstract: Objectives: Non-steroidal anti-inflammatory drugs are among the drugs with the highest prevalence of use (with or without prescription). While a notable percent of patients have incomplete knowledge about appropriate use of over the counter drugs. The aim of the current study was to evaluate the pattern of over the counter use of non-steroidal anti-inflammatory drugs and also the public knowledge about different aspects of over the counter use of non-steroidal anti-inflammatory drugs such as adverse effects, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although this could be a limitation with underrepresentation of the older population of participants who may have higher or lower prevalence of NSAIDS use. This might not be of great importance, as previous studies have shown that younger patients are more frequent users of NSAID medications [ 12–14 ]; Also may be attributed to the fact that older people are more likely to suffer from comorbidities [ 15 ] and may therefore be wary of taking NSAIDs, the increased patient education of NSAID-related side-effects during doctor appointments could have attributed to the less use too.…”
Section: Discussionmentioning
confidence: 99%
“…Although this could be a limitation with underrepresentation of the older population of participants who may have higher or lower prevalence of NSAIDS use. This might not be of great importance, as previous studies have shown that younger patients are more frequent users of NSAID medications [ 12–14 ]; Also may be attributed to the fact that older people are more likely to suffer from comorbidities [ 15 ] and may therefore be wary of taking NSAIDs, the increased patient education of NSAID-related side-effects during doctor appointments could have attributed to the less use too.…”
Section: Discussionmentioning
confidence: 99%